The Effect of Job Mutation and Job Rotation on Employees’ Performance at PT PLN Humbang Hasundutan District Area - Erna Oktaviani Simamora; Dionisius Sihombing (Jurnal Ekonomi dan Bisnis Digital, 2023)
The aim of this study was to know The Effect of Job Mutation and Job Rotation on Employee Performance at PT PLN Humbang Hasundutan District Area. The population in this study are employees at PT PLN Doloksanggul. The sampling technique used is Purposive sampling. The data collection techniques that used are interview, observation and questionnaires. The data analysis techniques used is multiple linear regression model with hypothesis testing t test, f test and coefficient of determination. The data has been tested using the validity and reliability test also classical assumptions. The data was processed using SPSS 22.0 for windows. The results of this study shows that Job mutation affect the employee performance in the amount of 55.6%. Job rotation affect the employee performance in the amount of 39.2%. Job mutation and job rotation simultaneously the employee performance the amount of 32.7%.